Model TangselPay Receipts Using the UTAUT 2 Method - Ikhwanudin, Aolia; Kusrini, Kusrini; Prasetio, Agung Budi (JOIN (Jurnal Online Informatika), 2021)
The South Tangerang City Government launched a digital financial service called TangselPay. This payment instrument will function as a means of paying levies and other transactions paid by taxpayers, TangselPay is basically a service from the South Tangerang City Government which is accessed via cellular phones (cell phones/smartphones) with the main aim of providing convenience to taxpayers in making levy payments. . . , so that taxpayers do not need to pay cash to the officer. This study aims to determine what factors influence people's interest in using TangselPay services in South Tangerang. The research model used is a modified model of Unified Theory of Acceptance and Use of Technology 2 (UTAUT 2). Data collection using purposive sampling method with the number of respondents in this study as many as 116 people in our market Pamulang. The data analysis technique in this study used Structural Equation Modeling (SEM) with SmartPLS version 3.3.3 software. The results of the analysis illustrate that the variables of Performance Expectations (PE) and Facilitation Condition (FC) have a positive effect on Use behavior and interest in use have a positive effect on usage behavior. While the variables of business expectations, social influence and hedonic motivation do not have a direct effect.